2019
DOI: 10.3390/reports2030017
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pro-Adrenomedullin as a Marker of Severe Bacterial Infection in Children: A Review

Abstract: Sepsis is still related to high mortality and hospitalization rates in the paediatric population despite medical progress. Prompt recognition of sepsis and consequent initiation of an appropriate treatment are essential elements in securing a positive outcome in adults and children. In such scenario, various biomarkers have been studied to support the clinician in the diagnosis of severe infections, in the identification of patients at risk of progression towards sepsis as well as in the evaluation of the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Cases characterized by reduced glomerular filtration and renal failure have also been reported to be associated with increased ADM levels (Jordan et al 2014). Furthermore, the glucocorticoid hormone, lipopolysaccharides found in the cell wall of Gram-negative bacteria (Garayoa et al 2000), cytokines (Ghobrial et al 2020), anoxia, and inflammation-induced oxidative stress also cause increased ADM levels (Fahmey et al 2018, Garazzino et al 2019. ADM is known to have antibacterial and anti-inflammatory effects (Akpınar et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cases characterized by reduced glomerular filtration and renal failure have also been reported to be associated with increased ADM levels (Jordan et al 2014). Furthermore, the glucocorticoid hormone, lipopolysaccharides found in the cell wall of Gram-negative bacteria (Garayoa et al 2000), cytokines (Ghobrial et al 2020), anoxia, and inflammation-induced oxidative stress also cause increased ADM levels (Fahmey et al 2018, Garazzino et al 2019. ADM is known to have antibacterial and anti-inflammatory effects (Akpınar et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Adrenomedullin is classified under the family of the calcitonin gene-related peptides (CGRP) (Geven et al 2018). In the body, ADM is produced in multiple tissues (Valenzulea-Sanchez et al 2016, Geven et al 2018, including the pulmonary tissue (Garazzino et al 2019). ADM has vasodilator (Akpınar et al 2014), diuretic and natriuretic (Rey et al 2013), bronchodilator (Önal et al 2018), antimicrobial (Garazzino et al 2019), antifungal andantiinflammatory (Akpınar et al 2014) effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADM is synthesized and released during sepsis (Jordan et al, 2014). In addition, ADM also has antimicrobial (Garazzino et al, 2019), antifungal, and anti-inflammatory effects (Allaker et al, 2006;Miguel et al, 2011;Bernal-Morell et al, 2018). Mid-regional-pro-adrenomedullin (MR-Pro-ADM) is a 48-amino acid fragment that shows the activity and level of ADM (Stolz et al, 2008;Miguel et al, 2011;Abd Elmouttaleb et al,2016;Valenzulea-Sanchez et al, 2016).The half-life of MR-Pro-ADM is higher than that of ADM.…”
Section: Introductionmentioning
confidence: 99%
“…Research assessing MR-proADM as a predictive diagnostic biomarker has been increasing in recent years with researchers investigating its role in paediatrics. A recent systematic narrative review suggested that MR-proADM may have a diagnostic role in the diagnosis of serious bacterial infections (non-IBI) in children as well as in non-infective inflammatory conditions such as juvenile arthritis [ 17 ]. However, a systematic review is required to determine if sufficient research exists to describe the role of MR-proADM in the diagnosis of IBI in children.…”
Section: Introductionmentioning
confidence: 99%